2018
DOI: 10.1152/japplphysiol.00377.2018
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic characteristics of postural hyperventilation: POTS with hyperventilation versus panic versus voluntary hyperventilation

Abstract: Upright hyperventilation occurs in approximately 25% of our patients with postural tachycardia syndrome (POTS). Poikilocapnic hyperventilation alone causes tachycardia. Here we examined changes in respiration and hemodynamics comprising cardiac output (CO), systemic vascular resistance (SVR) and blood pressure (BP) measured during head-up tilt (HUT) in 3 groups: patients with POTS and hyperventilation (POTS-HV), patients with Panic Disorder who hyperventilate (Panic), and healthy controls performing voluntary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…24). Returning to breathing in POTS, we have shown that respiratory response to pain or panic is a combination of hyperpnea and tachypnea consistent with the literature ( Stewart et al, 2018c , 2018a ). In contrast, minute volume increased in POTS patients who exhibited postural hyperpnea during tilt-table test by an increase in tidal volume with either no change or a small decrease in respiratory rate.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…24). Returning to breathing in POTS, we have shown that respiratory response to pain or panic is a combination of hyperpnea and tachypnea consistent with the literature ( Stewart et al, 2018c , 2018a ). In contrast, minute volume increased in POTS patients who exhibited postural hyperpnea during tilt-table test by an increase in tidal volume with either no change or a small decrease in respiratory rate.…”
Section: Introductionsupporting
confidence: 91%
“…Patients presenting with dyspnea but without evidence of cardiopulmonary disease on standard tests (electro- and echo-cardiogram, pulmonary function tests, chest radiograph) are often diagnosed with hyperventilation syndrome (HVS), anxiety, or panic. Yet, we now know that breathing in panic disorder differs from breathing pattern(s) seen in patients with POTS ( Stewart et al, 2018c ) ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Third, a large number of studies using transcranial Doppler have shown that cerebral blood flow velocity is influenced by P ET CO 2 ( Del Pozzi et al, 2014 , Immink et al, 2014 , Laffey and Kavanagh, 2002 , Novak et al, 1998 , Sato et al, 2012 , Stewart et al, 2018a , Stewart et al, 2018b ). Using extracranial Doppler, this finding was also confirmed in our previous study ( van Campen et al, 2020c ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this predominance appears to be disease-dependent. For example, in postural tachycardia syndrome (162), idiopathic hyperventilation syndrome (69), and a genetic brain disorder known as Rett syndrome, characterized by breathing instability (1,147), peripheral chemoreflex hyperreflexia manifests as hyperventilation. Its excessive sensitivity and tonicity may also contribute to the sensation of dyspnoea (35,164).…”
Section: Clinical Significance Of the Logic In Carotid Body Signalingmentioning
confidence: 99%